Optimizing the Capital Structure of Coal Companies in Indonesia Towards the Implementation of Government Regulation No. 36 of 2023 concerning Foreign Exchange Proceeds from Exports - Heny Istiqomah; I Ketut Gunarta (Journal Research of Social Science, Economics, and Management, 2025)
This study examines the impact of Government Regulation No. 36 of 2023 on the financial structure of PT X, a coal mining company in Indonesia, and explores how the company can optimize its capital structure to adapt to the new regulation requiring exporters to deposit 30% of their export proceeds into a special account for a minimum of three months. The research uses a quantitative approach with financial modeling, supported by qualitative interviews with PT X’s finance team and management. This research aims to analyze PT X's financial condition after implementing PP No. 36/2023 and to determine an optimal capital structure. The study uses a capital structure optimization method employing the Solver linear programming tool in Microsoft Excel. Its objective is to minimize the cost of capital while ensuring the company maintains a positive cash balance each month. The results indicate a significant shift in PT X's capital structure, with increased debt in 2023 due to the need for short-term financing to comply with the new regulation. The presence of bank loans will impact the company's capital structure, thus necessitating optimization. The results of this capital structure optimization indicate the percentage of funds PT X should obtain from loans versus the percentage from owner's equity. All financial ratios, specifically the current ratio, DER (Debt-to-Equity Ratio), and DSCR (Debt Service Coverage Ratio), showed improvement. However, the challenges to pure cash flow stability (cash ratio) were not entirely resolved.